Investigation of brittle fractures, interfacial kinetics and void formation in lead-free solders - Chin, Yoong Tatt (2014)
The aim of this thesis includes study the interfacial interactions of Lead-free solders (Pb-free) with the ENIG surface finish and its impact to brittle fracture of the solder joints. Selection of Pb-free solders through optimization the percentage composition of Sn-Ag-Cu solders and its alloying additions to provide resistant to Mechanical shock performance. It is desirable that some solder alloying design rules may be formulated to minimize the formation of interfacial defects (nano voids). Based on the data collected, a diffusion model will be constructed using Numerical Analysis to provide an understanding of the mechanism of nano-void formation.